ANALISIS PENJADWALAN PRODUKSI MENGGUNAKAN METODE NAWAZ ENSCORE HAM (NEH) DAN HEURISTIC POUR DALAM MEMINIMUMKAN TOTAL WAKTU PRODUKSI - DAMAYANTI, ROSA AZIZAH; TASTRAWATI, NI KETUT TARI; SARI, KARTIKA (E-Jurnal Matematika; Vol 12 No 3 (2023)DO - 10.24843/MTK.2023.v12.i03.p422, 2023)
Competition in the industrial world is getting tougher, requiring companies to have the right strategy and planning in every production activity. CV. Puspa is a company engaged in rice production. CV. Puspa uses the First Come First Serve (FCFS) method in scheduling every job that comes. This research aims to minimize the total production time using the Nawaz Enscore Ham (NEH) and Heuristic Pour methods at CV. Puspa. The data used is quantitative data, namely data on the processing time for rice production during January 2021. Based on the results of a comparison of the total completion time with the efficiency index parameter, the NEH method shows better performance compared to the FCFS and Heuristic Pour methods as on January 19, 2021. Meanwhile, based on the results of hypothesis testing with the F test, it shows that the FCFS, NEH and Heuristic methods Pour has the same efficiency. Thus, in general the results of scheduling for January 2021 using the NEH method do not have significant an influence on the production scheduling used by CV. Puspa.